Prevention Behavior of The Covid-19 Protocol In Palu Barat District; Thought and Feeling Theory - Rasyika Nurul Fadjriah; Shendy Krisnasari (Journal of Health and Nutrition Research, 2022)
Entering the third year, the trend of COVID-19 cases has again increased. Sourced from the WHO page, the total confirmed positive for COVID-19 in Indonesia until November was 6,582,291 cases (WHO, 2022). The purpose of this study was to see an overview of thoughts and feelings, personal references, human resources, and the culture of Palu City regarding implementing the COVID-19 protocol. The research method used a qualitative type with the technique of determining the informant was Purposive Sampling with the criteria such as age 18-40 years, domiciled in the West Palu District area, and willingness to become an informant. The number of informants was 23 regular informants, 1 key informant, and 1 additional informant. Data validation used source triangulation, and analysis used content analysis. The study showed that thoughts and feelings play a major role in COVID-19 prevention behavior; when cases soar high, the protocol was carried out as recommended, but when entering the new normal, it seems that it has begun to experience relaxation. Even though cases have increased, the COVID-19 protocol has not been appropriately implemented. Personal references, such as the role of the task force chairperson, community leaders, and youth leaders, provide examples and motivation to the community. Resources in the form of the role of health workers and adequate facilities at a time when cases are increasing but slowly decreasing, and even handwashing facilities were no longer found at this time. The specific culture was not seen in this study